The Potential Microbe Agent to Degrade Naphtalene and Phenanthrene in Dumai Oil Sludge : A Growth Response Test - Hardianti, Alfi Rizca; Sawitri, Dita Widiyanti; Lusiana, Helga (Graduate School, Universitas Brawijaya, 2019)
This study aims to find the most appropriate indigenous bacteria as Naphthalene and Phenanthrene degrading agents carried out in the growth response test. This research is very important to find the best bacterial agent, which in the future can reduce the impacts of oil pollution, as well as from the presence of oil sludgeBacterial cultures added in the media as much as 5% (v / v), which had previously been measured OD660nm = 0.5. The growth response test was carried out by growing 20 mL of bacteria in AMS media which was added with PAH substrate, naphthalene or Phenanthrene in various concentrations: 200 ppm, 500 ppm, 800 ppm, and 1000 ppm. In the naphthalene substrate with 24-hour incubation, the best treatment was in isolates A with a concentration of 200 ppm. In the phenanthrene substrate 24 hours incubation, the best treatment was in isolate A at 200 ppm, and at 48 hours incubation. Bacterial isolates F in 24-hour incubation increased growth in all treatments and controls. The bacterial E isolate on the phenanthrene substrate at 24-hour incubation has increased growth, which occurs until the incubation time is 48 hours, both in the control and phenanthrene substrate. E Isolate is tolerant of increasing substrate concentrations up to 1000 ppm, both naphthalene and phenanthrene and has the best growth ability. It can be concluded that isolate E has the best growth ability and is tolerant of increasing substrate concentrations up to 1000 ppm. E isolates were designated as the best isolates of naphthalene and phenanthrene degradation.Keywords: Dumai, Growth Response, Naphthalene, Phenanthrene